Enhancement of upconversion luminescence in lithium niobate polycrystal via doped potassium ion. Issue 7 (9th August 2017) - Wang, Rui; Liu, Zhihua; Li, Yuemei
ABSTRACT: Lanthanide ions doped lithium niobate has many outstanding performances in upconversion (UC) emission. However, the low UC efficiency still constitutes the main limitation for practical applications. To improve the issue of low efficiency, whether visible green UC emission in holmium/ytterbium/lithium niobate can be improved through tridoping with 0, 2, 4, 6, 8, and 10 mol% potassium has been investigated. The results demonstrate that increasing the concentration of potassium ion enhances the fluorescence signal by 20 times of visible green UC emission and that the maximum fluorescence signal can be achieved at 8 mol%. Theoretical analysis, arising from the steady-state rate equations, proves that the enhancement of green UC fluorescence signal is due to the increased lifetime of the intermediate ( 5 I6 ) state of the holmium ion and excited ( 5 F5/2 ) state of the ytterbium ion.